An analysis of the current deflection around Dongsha Islands in the northern South China Sea. Issue 1 (31st January 2013) - Wang, Dongxiao; Wang, Qiang; Zhou, Weidong; Cai, Shuqun; Li, Li; Hong, Bo
Abstract : [1] Based on the in situ data and ADCP observation in fall, it is found that a northeastward current at inter‐middle level flows on the Northern South China Sea (NSCS) continental shelf. This current flows almost along the isobaths, and it deflects from the isobaths veering toward deep water when flowing over the Dongsha Islands. Geographic currents derived from the climatologic hydrography data (WOA01) and absolute dynamic topography (ADT) data confirm the deflection of the northeastward current on NSCS continent. A fine resolution regional ocean model which can well reproduce the large scale circulation in the NSCS is used to analyze the dynamic about the deflection. The vorticity term balances shows that JEBAR (Joint Effect of Baroclinicity and Relief) drives the water column to depart from the isobaths. To the east of the Dongsha Islands, the isopycnal is almost orthogonal to the isobaths. The joint effect of the topographic and the baroclinic effect supplies negative vorticity and drives the water column to deflect from the isobaths and veer to deeper water. Momentum analysis along the stream line shows that, when the sea water flows around the Dongsha islands, the pressure gradient along the isobath pushes the sea water to accelerate, and then the Coriolis force orthogonal to the isobath increases and overcomes the corresponding pressure gradient, which drives the water deflected from the isobath toward the deep sea. Key Points: Mid‐level current on NSCS deflects from isobath around Dongsha Islands, in fall The vorticity balance shows that The JEBAR term is the dominant driving force Momentum balance shows the along isobath pressure gradient is the active force